Working memory performance of older adults with insomnia. (21st November 2012) - Lovato, Nicole; Lack, Leon; Wright, Helen; Cant, Megan; Humphreys, Joanne
Summary: Older individuals suffering insomnia typically report declines in their cognitive performance beyond what they consider to be normal changes due to the aging process. Recent neuro‐imaging studies have demonstrated frontal lobe hypo‐activation among insomniac populations when compared with healthy, good sleepers. However, research is yet to confirm whether frontal lobe hypo‐activation translates into objective declines when performing tasks hypothesized to draw upon this brain region. This study aimed to investigate whether older insomnia sufferers demonstrate significantly impaired performance on a challenging working memory task when compared with age‐matched good sleepers. Forty‐nine older individuals (mean age = 69.43 years, SD = 4.83) suffering from sleep maintenance insomnia were compared with 49 age‐matched good sleepers. Cognitive performance was assessed using the Double Span Memory Task, a computer‐based working memory task that requires participants to indicate the names and/or spatial locations of increasingly longer sequences of visually presented objects. After controlling for general intelligence, the individuals suffering from insomnia did not perform differently when compared with the good sleepers on either the simpler or more cognitively demanding components of the task. Older individuals with insomnia did not display an observable impairment of working memory in this study relative to good sleepers. Despite the mixed results from previous research, this study adds weight to the absence of objective impairment in insomniacs, at least while performing short‐term demanding cognitive tasks.